2008
DOI: 10.1111/j.1442-2018.2008.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fatigue in Chinese nurses

Abstract: Factors predicting fatigue in Chinese nurses were examined in a descriptive, correlational study. The participants were 581 nurses working in general hospitals in Chengdu City, China. The study instruments included the Occupational Fatigue Exhaustion Recovery Scale, the Job Content Questionnaire, the Exposure to Hazards in Hospital Work Environments Scale, the Pittsburgh Sleep Quality Index, the Job Dissatisfaction Scale, the Beck Anxiety Inventory, and the Beck Depression Inventory. The data were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
69
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 38 publications
8
69
2
1
Order By: Relevance
“…Work‐related factors, such as job demands, job control, support at work, physical work environments, and shift work were confirmed to contribute to acute or chronic fatigue in nurses (Samaha et al. 2007, Fang et al. 2008, Yuan et al.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Work‐related factors, such as job demands, job control, support at work, physical work environments, and shift work were confirmed to contribute to acute or chronic fatigue in nurses (Samaha et al. 2007, Fang et al. 2008, Yuan et al.…”
Section: Introductionmentioning
confidence: 93%
“…Insufficient recovery between work shift has been confirmed as a predictor of chronic fatigue (Winwood et al. 2006b, Fang et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress levels among professional nurses have increased in recent years due to the demands of clinical nursing. Previous studies have shown that work demands and stress are associated with adverse mental health such as emotional exhaustion 1) , depressive disorder 2,3) and fatigue 4,5) , which result in sleep problems and sickness absence 1) . Stress systems in the body, like the sympathetic-adrenomedullary system and the hypothalamic-pituitary-adrenocortical axis, start working, using adapted processes as the stress attracting 6) , and exhaustion tend to result from longterm exposure.…”
mentioning
confidence: 99%
“…Factors influencing fatigue of nurses have been studied extensively and work-related factors, psychological factors, and demographic factors have been recognized as contributing to nurse fatigue [2,3,4]. It is important for night shift workers not to perturb biological rhythms.…”
Section: Introductionmentioning
confidence: 99%